2018
DOI: 10.22491/rca.2018.2649
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de proteína bruta na dieta de juvenis de matrinxã (Brycon amazonicus)

Abstract: Aquicultura Carcaça Crescimento Peixes nativos Exigência proteica KEYWORDS Aquaculture Carcass Growth Native fishes Protein requirement RESUMO: Este estudo teve como objetivo avaliar o efeito de níveis de proteína bruta sobre o desempenho de crescimento e composição corporal de juvenis de Brycon amazonicus. Quatro dietas experimentais foram formuladas contendo níveis crescentes de proteína bruta (PB) em 30, 35, 40 e 45%. Cada dieta foi fornecida a três grupos de juvenis de Brycon amazonicus, peso médio de esto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Higher levels of crude protein resulted in better use of the energy by fish. Mattos, Bueno, Honczaryk, Pereira-Filho, and Roubach (2018) reported that protein levels from 40 to 45% may provide a satisfactory growth to juveniles of matrinxã due to the positive influence on energy metabolism. The same authors also commented that, at this stage, matrinxã present a high demand for protein to meet its requirements of protein and energy.…”
Section: Resultsmentioning
confidence: 99%
“…Higher levels of crude protein resulted in better use of the energy by fish. Mattos, Bueno, Honczaryk, Pereira-Filho, and Roubach (2018) reported that protein levels from 40 to 45% may provide a satisfactory growth to juveniles of matrinxã due to the positive influence on energy metabolism. The same authors also commented that, at this stage, matrinxã present a high demand for protein to meet its requirements of protein and energy.…”
Section: Resultsmentioning
confidence: 99%
“…que ocorre principalmente na Amazônia Central, costuma habitar as áreas alagadas e utiliza o canal do rio para sua migração (BENACON et al, 2015). A espécie tem hábito alimentar de caráter onívoro, no qual os juvenis preferem insetos e restos de animais ou plantas, já os adultos as frutas e sementes (MATTOS et al, 2018). Realizam uma migração trófica pela floresta alagada durante a enchente, época de reprodução e possui desova total (NAKAUTH et al, 2016).…”
Section: Discussionunclassified
“…This leads to lower feed consumption and productivity, as well as higher feed conversion. Mattos et al (2018) evaluated the effect of different levels of crude protein (30, 35, 40 and 45%) on juvenile matrinxã (approximately 3 g) in a continuous ow system. The study found no signi cant difference in the performance of the animals fed the three highest levels of crude protein in the diet.…”
Section: Zootechnical Performance Somatic Indices and Blood Parametersmentioning
confidence: 99%